Effects of Choir Spacing and Riser Step Heights on Acoustic and Perceptual Measures of SATB Choir Sound Acquired From Four Microphone Positions in Two Performance Halls. (October 2019) - Daugherty, James F.; Grady, Melissa L.; Coffeen, Robert C.
We assessed the effects of singing in two venues on acoustic and perceptualmeasures of performances by an SATB choir ( N = 28) as it sang in three spacing conditions, on two different riser unit heights, with data acquired from four microphone locations in each hall. Among primary acoustic results, long-term average spectra measures yielded a systematic pattern of significant contrasts between close and spread spacing conditions, with decreasing high-frequency energy as space between singers increased, regardless of venue, riser unit, or microphone location. Unlike previous findings with 12-in. (0.30-m) riser step heights, a doubled 16-in. (0.41-m) height did not enhance this pattern. Primary perceptual results were as follows: (a) All choristers (100%) thought spread singer spacing facilitated best hearing of their own voices in relation to the rest of the ensemble. (b) Nearly all singers (96%) reported their most comfortable vocal production in spread spacing. (c) All choristers thought the doubled riser step heights influenced choral sound, but 78% described vocal production as most comfortable with spread spacing on the regular riser unit. We discuss results in terms of implications for choral pedagogy and directions for future research.